A prophet in politics : a biography of J.S. Woodsworth - McNaught, Kenneth, 1918-1997 (Reprints in Canadian history., 2001)
In this elegant and rigorously researched work, Kenneth McNaught details the life, work, and principles of J.S Woodsworth and shows the powerful moral and political force that the pacifist, Methodist thinker exerted on Canadian politics. Woodsworth first went to the House of Commons in 1922, and became leader of the Cooperative Commonwealth Federation at its formation in 1933. A socialist to the end, he exhibited his anti-war convictions to Parliament, when, in 1939, he alone spoke out against joining the war in Europe. Woodsworth's ideas and strong social conscience helped to shape the development of the welfare state in Canada, and have left an intellectual legacy in both socialist and liberal circles. A Prophet in Politics marks the progress of socialism in Canada, as well as the economic and political conditions in the first half of the twentieth century. McNaught, who died in 1997, is himself an important figure in Canadian history, having fought as a professor of history for academic freedom and having brought the scholarly discussion of national politics into the public sphere. At the time of its original publication, Globe and Mail reviewers called it 'a definitive biography that in drama and organization ranks with the best books about the makers of Canada.' This edition, presented in the 'Reprints in Canadian History' series, includes a new introduction by Allen Mills.